Risk of the watch-and-wait concept in surgical treatment of intraductal papillary mucinous neoplasm - Tjaden, Christin; Sandini, Marta; Mihaljevic, André Leopold; Kaiser, Jörg; Khristenko, Ekaterina; Mayer, Philipp; Hinz, Ulf; Gaida, Matthias; Berchtold, Christoph; Diener, Markus K.; Schneider, Martin; Mehrabi, Arianeb; et al. (JAMA surgery, 2021)
The natural history of intraductal papillary mucinous neoplasms (IPMNs) remains uncertain. The inconsistencies among published guidelines preclude accurate decision-making. The outcomes and potential risks of a conservative watch-and-wait approach vs a surgical approach must be compared.To provide an overview of the surgical management of IPMNs, focusing on the time of resection.This cohort study was conducted in a single referral center; all patients with pathologically proven IPMN who received a pancreatic resection at the institution between October 2001 and December 2019 were analyzed. Preoperatively obtained images and the medical history were scrutinized for signs of progression and/or malignant features. The timeliness of resection was stratified into too early (adenoma and low-grade dysplasia), timely (intermediate-grade dysplasia and in situ carcinoma), and too late (invasive cancer). The perioperative characteristics and outcomes were compared between these groups.Timeliness of resection according to the final pathological findings.The risk of malignant transformation at the final pathology.Of 1439 patients, 438 (30.4%) were assigned to the too early group, 504 (35.1%) to the timely group, and 497 (34.5%) to the too late group. Radiological criteria for malignant conditions were detected in 53 of 382 patients (13.9%), 149 of 432 patients (34.5%), and 341 of 385 patients (88.6%) in the too early, timely, and too late groups, respectively (P < .001). Patients in the too early group underwent more parenchyma-sparing resections (too early group, 123 of 438 [28.1%]; timely group, 40 of 504 [7.9%]; too late group, 5 of 497 [1.0%]; P < .001), while morbidity (too early group, 112 of 438 [25.6%]; timely group, 117 of 504 [23.2%]; too late group, 158 of 497 [31.8%]; P = .002) and mortality (too early group, 4 patients [0.9%]; timely, 4 [0.8%]; too late, 13 [2.6%]; P = .03) were highest in the too late group. Of the 497 patients in the too late group, 124 (24.9%) had a previous history of watch-and-wait care.Until the biology and progression patterns of IPMN are clarified and accurate guidelines established, a watch-and-wait policy should be applied with caution, especially in IPMN bearing a main-duct component. One-third of IPMNs reach the cancer stage before resection. At specialized referral centers, the risks of surgical morbidity and mortality are justifiable.
Gesehen am 23.05.2023